Multiscale Observation of Two Polar Cap Arcs Occurring on Different Magnetic Field Topologies. Issue 8 (9th August 2020) - Reidy, J. A.; Fear, R. C.; Whiter, D. K.; Lanchester, B. S.; Kavanagh, A. J.; Price, D. J.; Chadney, J. M.; Zhang, Y.; Paxton, L. J.
Abstract: This paper presents observations of polar cap arc substructure down to scale sizes of meters and temporal resolution of milliseconds. Two case studies containing polar cap arcs occurring over Svalbard are investigated. The first occurred on 4 February 2016 and is consistent with formation on closed field lines; the second occurred on 15 December 2015 and is consistent with formation on open field lines. These events were identified using global‐scale images from the Special Sensor Ultra‐violet Spectrographic Imager (SSUSI) instruments on board Defense Meteorological Satellite Program (DMSP) spacecraft. Intervals when the arcs passed through the small‐scale field of view of the Auroral Structure and Kinetics (ASK) instrument, located on Svalbard, were then found using all sky images from a camera also located on Svalbard. These observations give unprecedented insight into small‐scale polar cap arc structure. The energy and flux of the precipitating particles above these arcs are estimated using the ASK observations in conjunction with the Southampton Ionospheric model. These estimates are then compared to in situ DMSP particle measurements, as well as data from ground‐based instrumentation, to infer further information about their formation mechanisms. This paper finds that polar cap arcs formed on different magnetic field topologies exhibit different behavior at small‐scale sizes, consistent with their respective formation mechanisms. Key Points: We compare observations (at multiple scales) of two polar cap arcs that are consistent with different formation mechanisms Small‐scale observations of polar cap arcs down to scale sizes of meters and temporal resolution of milliseconds are presented We find the small‐scale structures associated with the arcs in each event are very different, consistent with the formation mechanisms